REQUIREMENTS FORMED IN THE FIELD OF SOCIAL CONTROL IN THE FORM OF COMPETENCE: IMPLEMENTATION IN EDUCATION - Andrew N. Pechnikov (Russian State Vocational Pedagogical University, 2016)
RETRACTED ARTICLEThe aim of the investigation is to justify appropriate approach to the implementation of educational requirements formulated in the social management system in terms of competences. Methods. The methods involve analysis, synthesis and simulation. Results and scientific novelty. The main constraints of pedagogy opportunities to meet the requirements formulated in the field of social management are disclosed. The approach to the implementation of education of social management of the claims submitted in the form of competencies is proved. The roadmap reorientation of the educational process in the implementation of these requirements is given. Practical significance consists in the justification of the presence in the arsenal of Pedagogy and Psychology tested methods that meet the requirements formulated in terms of competences, and demonstrate the counterproductive existing voluntaristic approach to the introduction to the subject area of pedagogy and excessive foreign terms.